KIE Manfaat KMC (Kangaroo Mother Care) Untuk Perawatan Bayi Sehari-Hari Di Desa Bangun Rejo - Retno Wahyuni; Marliani; Isyos Sari Sembiring (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Kangaroo Mother Care (KMC) or Kangaroo Method Care (FMC) is a treatment for premature and low birth weight (LBW) infants with direct skin-to-skin contact, where the mother uses her body temperature to warm the baby. This method of care has also been shown to facilitate breastfeeding, increasing the length and duration of breastfeeding. The goal after the activity is that mothers who have babies and toddlers are exposed to material about Kangaroo Mother Care. IEC community service activities have been carried out in the form of counselling, providing information and education about the benefits of KMC and how to do KMC. This activity is expected not to end in community service activities, but with the leaflet media it can be used as a policy for related villages to develop in the form of applications as a course method for cadres in the health sector so that child health in the area can utilise the application in the implementation of courses for cadres, especially in the health sector.